Exchange bias effect in a finite site disordered canted antiferromagnet. (17th August 2018) - Pradhan, Suman Kalyan; Dalal, Biswajit; De, S K
Abstract: We report the temperature and magnetic field dependent magnetic properties of the single-phase polycrystalline La0.8 Sr0.2 Cr0.7 Ru0.3 O3 sample to explore the intrinsic magnetic phases of the sample. Our combined temperature and field dependent magnetization studies reveal the formation of ferromagnetic (FM) cluster-glass in the antiferromagnetic (AFM) matrix of host LaCrO3 . Interestingly, the as-studied sample exhibits both zero-field-cooled (horizontal shift) and field-cooled (vertical shift) exchange bias effects and, in both cases, magnitude of exchange bias field continuously increases with the decrease of temperature. Our successive hysteresis loop measurements completely ruled out the effect of any minor hysteresis loop and thus, establishes this vertical shift as conventional field-cooled exchange bias (CEB) effect, originating from the uncompensated spins of randomly substituted canted AFM spin structure. A significantly larger value of CEB field (7.5 kOe) at 5 K is achieved for a cooling field of 50 kOe, not usually observed in conventional FM/AFM interfacial exchange-bias systems.